Pengaruh Self Efficacy terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada PT. Taman Rekreasi Sengkaling UMM - Paulus Dakosta Yoman; Endi Sarwoko; Sri Wilujeng (Jurnal Riset Mahasiswa Manajemen, 2019)
This study aims to determine the direct effect between self efficacy on employee performance and the indirect effect of self efficacy on employee performance. , the data used are primary data from PT Taman Sengkaling UMM. The method used is descriptive quantitative, the number of respondents used was 73 respondents with a total statement of 31 statements. The analysis used is path analysis (path analysis). The results of the study use multiple regression analysis which shows direct self efficacy on employee performance and also indirectly on employee performance through job satisfaction.